EFEKTIVITAS AKTA PERDAMAIAN SEBAGAI ALTERNATIF PENYELEAIAN SENGKATA - Praningsih, Cerry (Ensiklopedia Education Review, 2025)
Abstract: The Peace Deed (Akta Perdamaian) is frequently utilized as an alternative dispute resolution mechanism in court, aiming to end conflicts amicably through mutual agreement between the parties. Under Indonesian positive law, this instrument holds permanent legal force equivalent to a court judgment, resulting in greater efficiency in terms of time and cost compared to lengthy and complex litigation processes. However, in practice, violations of the terms of the peace deed by one of the parties are not uncommon, which often leads to new disputes and complicates the previously agreed resolution. The central issues addressed in this paper are: To what extent is the peace deed effective in resolving disputes? and What are the legal consequences of using the peace deed as an alternative dispute resolution? This study employs secondary data sourced from books and academic journals, using a conceptual approach.Keywords: Peace Deed, Dispute Settlement, Breach of Agreement.